Rotas federativas para a promoção de capacidades estatais municipais: uma análise da experiência brasileira - Grin, Eduardo José (2016)
This thesis discusses how the Brazilian federalism promoted, from 1997 to 2014, initiatives to develop state capacity in municipalities. This theme was taken up on the federal agenda in the first government of Fernando Henrique Cardoso (1995-1998), continued during the two terms Lula (2003-2010), and finally, in the initial mandate of Dilma Rousseff (2011-2014). The decentralization of policies started in 1988 constitutes the political and institutional context which demands to modernize its management. It's presented how evolved the managerial and administrative qualification in the cities to situate the challenges of Brazilian cooperative federalism to support these level of government. This research was organized in three theoretical dimensions and analyzed five cases. The first dimension deals with the cooperation through territorial cooperative arrangements, regarding the Federal Joint Commitee (CAF), installed in 2003, as the object of analysis because brought together representatives from federal government and from municipalist associations. One of its fields of action was the developing of municipal state capacity. The second dimension addresses the federative cooperation by means of policy systems. It was compared the Unified Social Assistance System (SUAS), created in 2005, with the education policy, that is devoid of such systemic intergovernmental arrangement. In the education the analysis rests with Articulated Action Plan (PAR), instituted in 2007. The SUAS has a wide legislation and normatization aimed for municipal entities in which highlight demands to modernize the local bodies responsible for this policy. The goal is to compare if policy systems are more effective to promote state capacity than other kinds of federative relations. The third theoretical dimension concerns to federal programs generated to support the qualification in municipalities.The goal is to compare if policy systems are more effective to promote state capacity than other kinds of federative relations. The third theoretical dimension concerns to federal programs generated to support the qualification in municipalities. Were selected two programs: the Program of Management Modernization and Tax Administration and the Management of Basic Social Sectors (PMAT), administered by the BNDES since 1997, and the National Program of Support to the Administrative Modernization and Fiscal of Brazilian Municipalities (PNAFM), managed by the Ministry of Finance and the Federal Saving Bank (Caixa Econômica Federal) since 2001. The analysis in the three dimensions shows that, considering the comparative experience in international level, and the literature about federalism and intergovernamental relations, before the manner how were organized the territorial cooperation and the implementation of federal programs in Brazil, both modalities are not viable routes to further the modernization in municipalities. The research concludes that a national and articulated policy system, both for theoretical and empirical reasons, is the most appropriated type of federative cooperative institutionality to promote state capacity in the municipalities in realities such as Brazil. In this line, in the final of the Tesis it's proposed a analytical model that considers articulated policy systems as the most adequate model to deals with this federative challenge in a setting featured by the decentralization of policies, but that at the same time lives with a great heterogeneity and inequality of state capacity among local governments.